Acquisition of the non-generic definite article by Spanish learners of English as a foreign language - Isabelli-García, Christina; Slough, Rachel (Onomázein, 2012)
This study explains the acquisition of the non-generic uses of the english definite article the by L2 learners. Chilean university students completed a questionnaire containing deleted obligatory uses of the. in all, four identified categories showed to have different accuracy rates. Of the four categories, the one most similar to the L1 was the least difficult to acquire while the most different resulted as the most difficult. This concurs with other research and can be explained by L1 rules that are transferred to the L2.The other two categories did not show the same acquisition rate as compared to previous studies and cannot be explained by L1 transfer given that both languages share the same rules. Time spent studying the english increases accuracy rates across all categories. Knowing that difficulty with the definite article can be attributed to L1 interference is useful when implementing pedagogical recommendations to teach the english article system.